LANGUAGE STYLE ANALYSIS OF ROBERT FROST POEM CALLED “THE SOUND OF TREES” IN MOUNTAIN INTERVAL COLLECTION - Ratri Dwiningtyas Malik; Aulia Putri; Sri Langgeng Ratnasari; Linayati Lestari; Gandhi Sutjahjo (Universitas Riau Kepulauan, 2023)
The purpose of this study is to analyze the language style in Robert Frost’s poem called